P28 Development of a smartphone-based communication application to support, record, and share the process of ACP along with frailty evaluation. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Senda, K; Tadashi, W; Satake, S; Kinoshita, K; Takanashi, S; Matsui, Y; Nishikawa, M; Miura, H; Arai, H
Abstract : Introduction in the super-aged society, implementation of ACP is essential for people's sense of secure. The inter-disciplinary care team for frail older people in National Center for Geriatrics and Gerontology (NCGG) needs a communication tool for sharing the process of ACP. Methods: a smartphone-based communication application (SBCA) was developed to support, record, and share the process of ACP correctly and effectively among different care settings and various healthcare professionals. Results: SBCA enables to record a range of patients' values, goals, and preferences regarding future medical care, and preferred substitute decision-maker according to the words of patients using voice input system. Records are discussed at the inter-disciplinary care conference to confirm at each time point, and share the process of ACP. SBCA simultaneously records the descriptions of patients' medical problems, including the frailty status, and their responses by patients and families, or helpers, which indicate that patients have received enough explanations before ACP. SBCA renews records continuously and enables to activate ACP information confirmed among various healthcare professionals at any time of future incapacity, not just at the end-of-life. SBCA is developed to be added to the existing local health care information system, "Obu-chan Network", operating near NCGG, adhering the personal information protecting guideline. Feasibility of SBCA is examined by healthcare professionals using Obu-chan Network. The prototype of SBCA got favorable feedback at SBCA promotion conference in NCGG. Conclusion: we have developed SBCA to share the process of ACP along with frailty evaluation, which is supposed to provide genuine person-centered care.